Fractional Calculus and Certain Integral Transform of Extended $τ$-Hypergeometric Function - Jai Prakash Patel; Neelam Pandey (International Journal of Mathematics And its Applications, 2019)
In this paper, authors establish the some new integral and derivative formulas of generalized $τ$-hypergeometric functions $_3Γ_2 ^{τ} (z)$ defined by (R. K. Gupta {et al.} [3,4]). Furthermore by applying some integral transforms as Beta-transform, Verma transform, Whittaker transform, Laplace transform and $P_α$-transform on the resulting formulas.